PENDIDIKAN DAN TEKNOLOGI DALAM PERSPEKTIF AL QURAN - Yasmansyah, Yasmansyah; Sesmiarni, Zulfani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
On the one hand, in today's modern era, progress in the field of technology has helped human life a lot, which is a factor of progress and civilization, technology itself has developed through a research and development process that requires intellectual knowledge, experimentation and testing. The Qur'an has a universal and comprehensive content. Whether science and technology develops or not really depends on human activity in studying natural phenomena, studying kawniyah verses, and accompanied by qouliyyah verses. Al-Qur'an is a biological guide that leads humans to get a clear point of truth. The images contained in the Al-Qur'an are the motivation so that we can continue to explore it. From the generality of the verses of the Al-Qur'an it requires us to investigate what Allah has described in order to strengthen human belief that the Qur'an is indeed a book. instructions that will always be contextual & relevant in every era. No one can deny that the Qur'an only lays the basic rules of human life on the relationship with God by the creator, on the interactions between humans, and on their actions towards the natural world around them, but it also states what humans were created for